Setting Strategies In Social Networking Sites: Community-Based Indicators For Small And Medium Industries In Malaysia - Md Jani, Noraniza; Zakaria, Mohd Hafiz; Maksom, Zulisman; M. Haniff, Md. Shariff (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
Theconstant growth of data on social media that deals with the business nature generated by online communities has inundated business owners and marketers with business-related conversations. The consideration, preference, and action stages about brands and products are easily influenced by the community members in social networking sites (SNS), making the flow of information become multidirectional, interconnected, and difficult to predict. Therefore, firms and brands are called upon to attract the attentionof these communities by focusing on building, enhancing and maintaining interactions through an effective and strategic approach to SNS marketing. This paper will gain insights on such valuable information by integrating findings from both perspectives ofsmall and medium enterprises (SMEs) and engaged brand communities in SNS. Two distinct questionnaire surveys are conducted upon 30 SMEs and 30 active SNS customers in order to obtain more clarity. As a result, a spectrum of coalesced data was obtained andconcluded that the firms, brands and the brand's community must always give each other's continual commitment so that the nurturing relationships provide satisfactory mutual benefits to all community participants in the interest of increasing the overall brand performance.